Epistimologi Barat Modern: Dominasi, Kritik, dan Implikasi dalam Diskursus Ilmu Pengetahuan dan Pembangunan - Pamuji Pamuji; Azmy Abdurrahman; Ahmad Jaelani; Al Anshor; Setiyorini Setiyorini; Jusni Silalahi; Rina Setyaningsih (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This article explores a critical perspective on epistemology that has long been influenced by Western-centric biases, aiming to uncover its inherent discriminatory aspects. Employing a literature-based approach, the discussion centers on two primary concerns. First, the exclusionary nature of Western epistemology is inseparable from the ideals of modernity, which emphasize progress and innovation. These characteristics often marginalize alternative knowledge systems rooted in traditional or indigenous communities. Second, the discourse of development operates as a mechanism to perpetuate Western epistemological dominance, serving as a justification to reassert control over nations in the Global South or former colonies. The article concludes by emphasizing the importance of fostering a critical mindset among scholars, encouraging openness to diverse epistemological frameworks that reflect local contexts, without entirely dismissing the scientific traditions of the West.